2009
DOI: 10.1007/s10453-009-9140-8
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of IgE in children during ragweed pollination season

Abstract: Genetic and environmental factors are responsible for running allergic diseases. The aim of this study was to compare the values of total-(t-IgE) and allergen-specific IgE (s-IgE) to Ambrosia artemisiifolia L. (Amb a) in children with sensitization to Amb a during ragweed pollination season, who experienced seasonal symptoms of allergic rhinitis (rhinorrhea, post-nasal drip, nasal congestion, itching, sneezing) and asthma (coughing, especially at night, wheezing, shortness of breath, chest tightness). Ragweed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Some authors have confirmed the close relationship between the airborne pollen concentration and the allergic symptom score [6][7][8][9][10]. The above-mentioned authors have revealed an increase in the presence of symptoms when pollen counts were higher, while other authors have examined the relationship between airborne pollen and the prevalence of positive skin prick tests results [11,12,13,14] or sIgE levels in serum [14,15,16,17].…”
Section: Introductionmentioning
confidence: 93%
“…Some authors have confirmed the close relationship between the airborne pollen concentration and the allergic symptom score [6][7][8][9][10]. The above-mentioned authors have revealed an increase in the presence of symptoms when pollen counts were higher, while other authors have examined the relationship between airborne pollen and the prevalence of positive skin prick tests results [11,12,13,14] or sIgE levels in serum [14,15,16,17].…”
Section: Introductionmentioning
confidence: 93%
“… 17 AIT appears to have a clinical efficacy of up to 12 years and can prevent the development of asthma and hypersensitivity to novel allergens. 18 , 19 Indications for AIT with ragweed allergen extracts/preparations include: Verification of immunoglobulin E (IgE)-mediated sensitization – not necessarily monosensitization (combining skin testing, eg, skin prick test [SPT] and in vitro diagnostics 20 – total and allergen-specific IgE in serum, especially elevated levels of specific IgE to ragweed major allergen Amb a 1, as well as novel in vitro methods, such as basophil activation test, with elevated levels of activated and degranulated basophils in response to ragweed allergens)–with a clear relationship to clinical history (symptoms of AR, rhinoconjunctivitis, and asthma). Availability of standardized or in-house high-quality allergen preparations.…”
Section: Introduction To Ambrosia Artemisiifolia mentioning
confidence: 99%
“…Verification of immunoglobulin E (IgE)-mediated sensitization – not necessarily monosensitization (combining skin testing, eg, skin prick test [SPT] and in vitro diagnostics 20 – total and allergen-specific IgE in serum, especially elevated levels of specific IgE to ragweed major allergen Amb a 1, as well as novel in vitro methods, such as basophil activation test, with elevated levels of activated and degranulated basophils in response to ragweed allergens)–with a clear relationship to clinical history (symptoms of AR, rhinoconjunctivitis, and asthma).…”
Section: Introduction To Ambrosia Artemisiifolia mentioning
confidence: 99%